Bariatric surgery and hypertension: implications and perspectives after the GATEWAY randomized trial - Benaiges, David; Climent, Elisenda; Goday, Albert; Flores-Le Roux, Juana A.; Pedro-Botet, Juan (Cardiovascular Diagnosis and Therapy; Vol 9, No 1 (February 01, 2019): Cardiovascular Diagnosis and Therapy, 2018)
Obesity prevalence has presented an exponential increase in the last years, becoming a serious public health issue (1). Moreover, patients with an increased body mass index exhibit different comorbidities, including hypertension, which are tightly related to the high cardiovascular risk of this population (2).